2023
DOI: 10.1212/wnl.0000000000207264
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Metabolites With Racial Disparities in Hypertension and Stroke in the REGARDS Study

Abstract: Background and Objectives:In the United States, the risk of stroke is greater among Black compared to White individuals. However, the reasons for the difference in stroke incidence are not fully elucidated. We aimed to identify metabolites that account for higher prevalent hypertension and incident ischemic stroke among Black adults.Methods:We used a stroke case-cohort nested within the REasons for Geographic and Racial Differences in Stroke (REGARDS) study. Targeted metabolomic profiling of 162 plasma metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In addition, the metabolite measurements were quality controlled and normalized across batches by including human pooled plasma samples at regular intervals of every 10 injections. All metabolite level values were rank-based inverse normal transformed before statistical analysis since they did not conform to a normal distribution …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the metabolite measurements were quality controlled and normalized across batches by including human pooled plasma samples at regular intervals of every 10 injections. All metabolite level values were rank-based inverse normal transformed before statistical analysis since they did not conform to a normal distribution …”
Section: Methodsmentioning
confidence: 99%
“…All metabolite level values were rank-based inverse normal transformed before statistical analysis since they did not conform to a normal distribution. 22 , 23 , 24 …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, N -acetyl-tryptophan protects against hepatic ischemia-reperfusion injury through the RIP2/caspase-1/IL-1β signaling pathway; however, its effects on ischemic cardiomyopathy remain unclear. 44 Gluconic acid, a substance produced through the aerobic oxidation of glucose, 45 has been associated with oxidative stress, 46 hyperglycemia, and hypertension; 47 however, evidence directly linking it to CHD is unavailable. The potential relationship between these metabolites and CHD remains a vital and challenging research area.…”
Section: Discussionmentioning
confidence: 99%
“…This sampling design has been described and used in prior REGARDS studies. 11,[14][15][16][17][18] In this analysis, participants who were lost to follow-up, had a history of stroke at the time of enrollment, or had no plasma available for metabolite measurements were excluded. We also excluded participants with hemorrhagic stroke and those without a record of stroke type.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…13 Additionally, we demonstrated that a plasma metabolite, gluconic acid, linked hypertension, and incident ischemic stroke, specifically among Black adults, and was also associated with socioeconomic and behavioral measures. 14 These studies suggest the potential of the plasma metabolites, which may serve as biomarkers to reflect the lifestyle or health behaviors that impact the risk of stroke. Because LS7 is a parameter that reflects vascular health, we hypothesize that there are plasma metabolites that are associated with LS7 and link the LS7 with stroke risk.…”
mentioning
confidence: 99%